Alisma orientalis Beverage Treats Atherosclerosis by Regulating Gut Microbiota in ApoE-/- Mice - Boran Zhu; Yi Zhai; Mengjiao Ji; Yanan Wei; Jiafei Wu; Wenda Xue; Wei wei Tao; Haoxin Wu (Frontiers Media S.A., 2020)
BackgroundAlisma orientalis beverage (AOB) is a Chinese traditional medicine formulated with a diversity of medicinal plants and used for treating metabolic syndrome and atherosclerosis (AS) since time ago. Given the current limited biological research on AOB, the mechanism by which AOB treats AS is unknown. This study investigats the role of AOB-induced gut microbiota regulation in the expansion of AS.MethodsWe established an AS model in male apolipoprotein E-deficient (ApoE−/−) mice that are fed with a high-fat diet (HFD), treated with numerous interventions, and evaluated the inflammatory cytokines and serum biochemical indices. The root of the aorta was stained with oil red O, and the proportion of the lesion area was quantified. Trimethylamine N-oxide (TMAO) and trimethylamine (TMA) levels in serum were evaluated through liquid chromatography with mass spectrometry. Flavin−containing monooxygenase 3 (FMO3) liver protein expression was assessed by Western blotting. 16S rDNA sequencing technique was adopted to establish the changes in the microbiota structure.ResultsAfter 8 weeks of HFD feeding, an inflammatory cytokine, and AS development expression were significantly decreased in mice treated with AOB; the same parameters in the mice treated with the antibiotics cocktail did not change. In the gut microbiota study, mice treated with AOB had a markedly different gut microbiota than the HFD-fed mice. Additionally, AOB also decreased serum TMAO and hepatic FMO3 expression.ConclusionThe antiatherosclerotic effects of AOB were found associated with changes in the content of gut microbiota and a reduction in TMAO, a gut microbiota metabolite, suggesting that AOB has potential therapeutic value in the treatment of AS.